Keterampilan Kerja dan Sikap Kerja terhadap Efektivitas Kerja Karyawan - Titi Hasanah (IPM2KPE, 2022)
The purpose of this study was to determine the effect of work skills and work attitudes either partially or simultaneously on the work effectiveness of PT Sucofindo Lahat Lahat employees. This research method is quantitative. The sample in this study were 37 employees of PT Sucofindo Lahat. Data analysis with the help of SPSS program. The results showed that the results of the T test analysis showed that, a) the work skills variable on work effectiveness had a significance value of 0.038, which means sig (0.038) < (0.05); b) the work attitude variable on work effectiveness has a significance value of 0.005 which means sig (0.005) < (0.05). While the results of the F test showed a significant value of 0.001, meaning Sig (0.001) < (0.05). In conclusion, the variable of work skills, work attitude has a significant effect on the work effectiveness of PT Sucofindo Lahat. Also, work skills and work attitudes have a positive and significant effect on the work effectiveness of PT Sucofindo Lahat. Keywords: Work Effectiveness, Work Skills, Work Attitude